Grasshopper diversity in organic and conventional farm lands in Batu City, East Java, Indonesia - RISKA PUTRI QUROTAAYUNINA; AMIN SETYO LEKSONO; DWI SUHERIYANTO; WAHEED ALI PANHWAR (Society for Indonesian Biodiversity, 2026)
Abstract. Qurotaayunina RP, Leksono AS, Suheriyanto D, Panhwar WA. 2026. Grasshopper diversity in organic and conventional farm lands in Batu City, East Java, Indonesia. Biodiversitas 27 (3): d270339. https://doi.org/10.13057/biodiv/d270339. Grasshoppers are sensitive to environmental changes and can serve as effective bioindicators in agroecosystems. This study assessed their abundance, diversity, and community composition across different farm types and sampling times in organic and conventional farming systems, and evaluated their indicator potential. Surveys were conducted at six sites: Organic Fruit (OF), Conventional Fruit (CF), Organic Paddy (OP), Conventional Paddy (CP), Organic Vegetables (OV), and Conventional Vegetables (CV). At each site, sampling was performed using sweep nets across five plots during morning, noon, and afternoon periods. Data were analyzed using Generalized Linear Mixed Models to test differences in abundance, species richness, diversity, and dominance. Community similarity was evaluated using the Bray-Curtis index, species-environment relationships using Canonical Correspondence Analysis (CCA), and indicator species using the Indicator Value (IndVal) method. A total of 25 species comprising 5,636 individuals were recorded. Farm type significantly affected all community parameters (abundance, species richness, dominance and diversity), while sampling time influenced only abundance and species richness, with no significant interaction effects. The highest abundance, richness, and diversity were observed in organic fruit and organic paddy systems, whereas the lowest values occurred in conventional vegetable fields. Community composition was shaped by farm type and wind speed. Several species were found to have potential as group or individual indicator species, such as Anaxipha sp., and Phlaeoba infumata in OF; Caryanda spuria and Tagasta marginella in CF; Conocephalus fasciatus and Atractomorpha angusta in OP; and Oxya hyla in CP. No indicator species were identified in vegetable farms. Overall, the results demonstrate that organic farming supports higher grasshopper diversity and more structured communities, highlighting its importance for biodiversity conservation and the use of grasshoppers as ecological indicators.